Comparative study of big data of global adakites and mineralization-related granite in the Geza arc metallogenic belt, northwest Yunnan, Southwest China. Issue 3 (3rd July 2018) - Xuelong, Liu; Wenchang, Li; Qi, Zhang; Na, Zhang; Changzhen, Zhang; Ying, Luo; Shuaishuai, Wang; Fucheng, Yang; Jianhang, Chen; Zhenhuan, Li
ABSTRACT: The Geza arc is an important part of the Sanjiang tectono-magmatic belt and is a newly discovered copper polymetallic ore concentration area in northwest Yunnan province, Southwest China. The area comprises numerous metal ore deposits, including one super-large deposit, three large deposits, etc. The formation of these deposits was closely related to intermediate–acidic magmatic intrusions. Based on previous studies, the "big data" analysis technique was used for a comparative study of large geochemical datasets of granite related to ore-formation in the Geza porphyry copper deposit and global adakites. As a result, 1313 element combinations and 127, 765 overlap ratios were obtained. The results show that the Geza porphyry has similar geochemical characteristics to global adakites (the ratios of REE and Ga to major elements are in the range of global adakites). However, the Cu, Mo, and Zn contents of the porphyry are significantly higher than those of global adakites, and the porphyry may, therefore, represent an end-member of the global range of adakite composition. In addition, the geochemistry of adakites associated with the porphyry copper deposits overlaps in part with that of global adakites, although most of the data lie outside of the range of global adakites (i.e. low Mn/Cu, Sr/Cu, Na/Cu, and Zr/Cu values, and high Th/Cu, Ba/Cu, Na/Mo, Rb/Mo, Th/Mo, Ta/Mo, Ba/Mo, Mn/Zn, and Ba/Zn values). The samples with characteristics that deviate significantly from the geochemistry of global adakites show more advanced mineralization and alteration, and a stronger relationship with Cu and Mo mineralization. The results of geochemical data mining can be used as a prospecting indicator, and provide a new scientific basis for geological prospecting of the deep levels and periphery of the Geza Cu polymetallic ore belt.